The Incidence of Clubfoot in the Czech Republic: A Nationwide Epidemiological Study from 2000 to 2014 - Janatová, Klára; Nováková, Tereza; Lopot, František (Children (Basel, Switzerland), 2023)
Clubfoot is one of the most common musculoskeletal birth deformities worldwide. The prevalence varies among individual countries and populations. There is a lack of nationwide incidence studies in Central Europe. We analyzed the incidence of clubfoot in the Czech Republic over 14 years. Patients born with clubfoot in the Czech Republic were identified using The National Registry of Congenital Anomalies. Demographic data were included. Data from 2000 to 2014 were collected and analyzed regarding gender and regional distribution. The study's chosen time frame was grounded on the condition of the Czech industry. Following extensive transformations in 1989, the industry eliminated highly non-ecological operations with significant environmental impact and related health risks. The incidence of clubfoot during the study period was 1.9 (95% CI 1.8-2.0) per 1000 births; males comprised the majority (59%). The incidence significantly differed among individual regions of the Czech Republic (p < 0.001). The incidence in the Czech Republic was higher than in previous European studies. We found significant regional differences in incidence, which could indicate that there may be exogenous pathogenic factors. For this reason, we plan to follow up our work with an up-to-date study.
Keywords: epidemiology; clubfoot; incidence; foot deformity; congenital talipes equinovarus